Adaptive Physical Education Teachers' Profile in Indonesia: The Opportunity of Improving Adaptive Physical Education Status - Mahendra, Agus; Budiman, Didin; Stephani, Mesa Rahmi; Suntoda, Andi; Budiana, Dian; Lubay, Lukmanul Hakim; Slamet, Suherman; Sumarno, Gano; Wibowo, Ricky; Putri, Wulandari; Anira, Anira; Nugroho, Wildan Alfia (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
Concerns to children with disabilities in terms of their needs for moving and level of physical activity have not been supported by a teacher supply system that is appropriate for their field of study, namely adaptive physical education teachers. This study is aimed at portraying teachersâ€™ profiles of Adaptive Physical Education in special schools in Indonesia. The data collection was carried out by means of questionnaires and articulated with the descriptive approach. The result of the study reveals that the number of specialist teachers with physical education backgrounds is still meager, which is only around 38 percent, compared to those who graduated from Special Education Program, which more than 60.5 percent. The majority of the teachers have never been given a chance to improve their PE teaching competency in the form of training (86,4 percent). It is recommended that there should be an openness from those working in special schools and the Ministry of Education and Culture of the urgent need for this adaptive physical education teacher.Â  The statement will encourage the evolve of national urgency and drive all the stakeholders to respond to it institutionally, for instance by opening the program for adaptive physical education or at least to pave the way with initially offering concentration for this adaptive PE under the generic PE program.